The Impact Of Work Experience And Competence On The Performance Of Employees Of The South Tangerang City General Election Commission - Aathifah Fauziyyah; Sunarti (JURNAL MANAJEMEN MOTIVASI, 2026)
This study aims to analyze the impact of work experience and competence on the performance of employees of the General Election Commission (KPU) of South Tangerang City. Work experience and competence are used as independent variables, while employee performance is a dependent variable. The research method used is quantitative with an associative approach. Data was obtained through the distribution of questionnaires to 57 respondents of KPU employees of South Tangerang City. The results showed that work experience had a negative and insignificant influence on employee performance with a tcal value of -0.783 < ttable 2.004 and a significant value of 0.437 > 0.05. On the contrary, competence had a positive and significant effect on employee performance with a calculated value of 2.141 > 2.004 and a significant value of 0.037 < 0.05. Simultaneously, work experience and competence together have a negative and insignificant effect on employee performance with a value of Fcal 2.313 < Ftable 3.17 and a significant value of 0.109 > 0.05. These results show that competence is more dominant in improving employee performance compared to work experience. Therefore, competency development through training and skill improvement is the main factor in improving the performance of South Tangerang City KPU employees.